KANDUNGAN NATRIUM BEBERAPA JENIS SAMBAL KEMASAN SERTA UJI TINGKAT PENERIMAANNYA (THE SODIUM CONTENT OF SOME CHILLI SAUCES AND ITS SENSORY EVALUATION) - Suryana Purawisastra; Heru Yuniati (Persagi, 2010)
ABSTRACT Background: Chili sauce is one the spice which is widely used in Indonesia. In making of the sauce, salt is added to increase the palatability of the chili sauce. In the past salt was the only source of sodium, however, nowadays there are some food additives containing sodium such as sodium benzoate becoming the source of sodium. At the moment, the chili sauce are available in the market, and in making those sauces, beside the addition of salt is also some food additive containing sodium were added. The excessive of sodium intake is related to the risk of hypertension and kidney failure. Objectives: to analyze the sodium contents of 10 kinds of chili sauces available in the market and to evaluate the sensory of the sauce. Methods: Ten samples of chili sauce in various brands were bought from supermarket, and then analyzed its sodium content using the Flame photometer method. Its sensory evaluation was performed by the thirty-two of testers. Results: The sodium content of sauces was shown that the value of the content was varying significantly (p £ 0.05). The highest content was 9.03 mg per gram, and the lowest was 3.82 mg per gram. The others were spread out between the highest and the lowest. Whereas the sensory evaluation of the sauce indicated that the sauce containing the higher content of sodium was tend to be more acceptance than the lower one. Conclusion: The sodium content of sauces in this study was varying between 9.03 to 3.82 mg per 100 g, whereas the sensory evaluation of the sauces revealed that the sauce which contained the higher content of sodium was more preference by the testers than the lower one. [Penel Gizi Makan 2010, 33(2): 173-179] Keywords: sodium content, chili sauce, food additives.